Artificial Intelligence Applications in TV Industry Workflow - Guedes, Alan L. V. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2025)
The TV industry is going through a major change due consumers need for high-quality, diverse, and customized content. This leads to increase production costs while the production time shrink. To deal with these challenges, the industry is levering the use of Artificial Intelligence to improve and optimize their processes. This paper gives a summary of how it is being used in existing literature and publicly available use cases. But different than other works, we put them application in perspective of the TV Industry workflow of pre-production, production, post-production, and distribution.